The effect of intravenous magnesium sulfate infusion on reduction of pain after abdominal hysterectomy under general anesthesia: a double-blind, randomized clinical trial - Jarahzadeh, Mohammad Hossein (Electron Physician, 2016)
BACKGROUND: Post-surgical pain is a physiological response to tissue trauma that produces unpleasant physiological effects with manifestations on various organic systems. OBJECTIVE: According to the effect of magnesium sulfate on the N-methyl-d-aspartate (NMDA) receptor, this study examined the effect of magnesium sulfate on the reduction of pain and the mean amount of narcotics consumed by patients after abdominal hysterectomies. METHODS: This double-blind clinical trial study was performed on 60 patients who had undergone abdominal hysterectomies in Shahid Sadoughi Hospital in Yazd, Iran, from 2013 to 2015. The patients were divided randomly into two groups of 30 members each. All of the patients received 2 mg of Midazolam and 2 mcg/kg of Fentanyl as the induction of anesthesia with propofol (2–2.5 mg/kg) and Atracurium 0.5 mg/kg was conducted. All of the patients received 5 mg of intravenous morphine 30 min after induction of anesthesia. Afterwards, the study group received 50 mg/kg of magnesium sulfate in 500 cm(3) of Ringer’s serum during the 20 minutes, and 500 cm(3) of Ringer’s serum was administered to the members of the placebo group. Visual analogue scale VAS scores were evaluated to reach the minimum difference of 0.8 in mean pain score RESULTS: The results of this study indicated that the mean pain scores immediately after surgery and at 1, 2, 6, and 12 hr after surgery were lower in the study group than in the placebo group. The mean value of narcotic consumption at all measured time points was higher in the placebo group. No significant differences were found between two groups concerning drug complications. CONCLUSION: The results of this study indicated that the intravenous injection of magnesium sulfate can reduce pain, reduce morphine consumption, and reduce the side effects of morphine in patients after surgery. FUNDING: This study was funded by Shahid Sadoughi University of Medical Sciences, Yazd, Iran CLINICAL TRIAL REGISTRATION: The trial was registered at the Thai Clinical Trials Registry (http://www.clinicaltrials.in.th) with the registration ID: TCTR20160308001.